Doing good: Local and global understandings of Buddhism in Hong Kong’s Umbrella Movement - Westendorp, Mariske (Journal of global buddhism, 2020)
In this paper, I present Hong Kong Buddhism as a construct of modernity, particularly in its emphasis on tradition. 'Modern Buddhism' shapes how Buddhists in the city reflect on their religion and their being in the world. The latter is seen in how Hong Kong Buddhists responded to the 2014 Umbrella Movement. Although the Umbrella Movement was in essence a political movement seeking universal suffrage, it indirectly highlighted the importance of religion in the everyday lives of Hong Kong middle-class residents. While some Buddhists went to the protest sites, others stayed at home to meditate, and many decided to disengage from the protests altogether. While differing in terms of civic engagement, there is significant similarity in these narratives regarding the perception of how to act as 'good' Buddhists.